2010
DOI: 10.1002/cmdc.200900525
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Phthalimides as Immunomodulatory and Antitumor Drug Prototypes

Abstract: Ni‐Mn‐based Heusler alloys exhibit a variety of features related to martensitic transformations and are materials that are sought to be employed in actuation applications. To be able to exploit their properties, it is necessary to understand the rich variety and subtle magnetic coupling mechanisms occurring in these alloys. We review complementary neutron polarization analysis and ferromagnetic resonance experiments and give an account on the complex magnetism of these alloys in the austenite and martensite st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…In Sarcoma-180-bearing animal assays, only thalidomide and compounds It has been demonstrated that inhibition of angiogenesis and tumor growth by thalidomide or analogues requires metabolic activation [12,[41][42][43]. In a similar way, Pessoa et al [17] also suggest that a prior metabolic activation is necessary to produce one or more active metabolites from N-phthaloyl amino acids derivatives, explaining their antiproliferative activity on in vivo models only. Therefore, it is also possible that the metabolizing of the molecules also explains, at least in part, the in vivo antitumor action, since it is very known that some molecules undergo hepatic enzymatic reactions to generate active metabolites [44].…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…In Sarcoma-180-bearing animal assays, only thalidomide and compounds It has been demonstrated that inhibition of angiogenesis and tumor growth by thalidomide or analogues requires metabolic activation [12,[41][42][43]. In a similar way, Pessoa et al [17] also suggest that a prior metabolic activation is necessary to produce one or more active metabolites from N-phthaloyl amino acids derivatives, explaining their antiproliferative activity on in vivo models only. Therefore, it is also possible that the metabolizing of the molecules also explains, at least in part, the in vivo antitumor action, since it is very known that some molecules undergo hepatic enzymatic reactions to generate active metabolites [44].…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, immunomodulatory drugs based on thalidomide, mainly amino-substituted thalidomide analogs, have been reported to be superior candidates as antitumor agents [45,46]. Despite thalidomide had not led to spleen morphological alterations in this work, it is known that some phthalimide analogues are co-stimulatory substances, increasing the response of T-lymphocytes to T-cellreceptor-mediated stimulation, the production of interleukin-2 and interferon-γ as well as the number of natural killer cells [17,47]. On the other hand, most clinical chemotherapy drugs are immunosuppressive and has negative side effects [48], such as leucocyte suppression, hypoplasia of the splenic white pulp and small lymphoid aggregates in 5-FU-treated mice [46].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations